Determinação da quantidade de inoculo de azola e avaliação dos efeitos de sua consorciação sobre as características produtivas de dois cultivares de arroz - Ferreira de Carvalho, Edson; del Giudice, Renato Mário; Vieira, José Maria; Reis Condé, Alcides (Revista Ceres, 2025)
Two experiments were carried out during 1984/85 and 1985/86 in order to determine the inoculum quantity of Azolla microphylla that maximizes the productivity of azola biomass in association with two rice cultivars (INCA and IAC-435) and to evaluate the effect of this Pteridophyta on rice productivity.